Rancangan Meja Las dengan Penerapan Magnet Elektromagnetik untuk Meningkatkan Stabilitas dan Presisi Pengelasan - Ahmad Eko Suryanto; Marko Ayaki Lumbantobing; Sri Murwantini; Agung Samudra; Supriyadi Supriyadi (G-Tech: Jurnal Teknologi Terapan, 2025)
Precision is very important in the welding process to ensure that the welding results are strong and accurate. A sturdy and well-designed welding table is essential to maintain workpiece stability and precision in welding operations. The method used in this research is Research and Development (RnD) with the ADDIE model. This research aims to design a welding table with the application of electromagnetic magnets through literature study, design and testing of welding table prototypes. The result of the research is a welding table product with the application of electromagnetic magnets. Testing shows the use of electromagnetic magnets on the welding table can improve the stability and accuracy of welding results. This study also obtained data on user/practitioner satisfaction after using a welding table with electromagnetic magnets based on 12 important aspects which include Purpose, Specific, Measurable, Achievable, Relevant, Time-bound, Innovative, Functional, Efficiency, Reliability, Ease of Use, and Safety.